Role of inositol and its isomers in glucose metabolism - O.A. Nochvinа; E.V. Slyvka (Publishing House TRILIST, 2021)
Despite the chemical similarities between myo-inositol and D-chiro-inositol and their synergistic effects on insulin sensitivity, they serve different functions. Insulin resistance is one of the etiological factors in the development of polycystic ovary syndrome (PCOS), diabetes mellitus, metabolic syndrome, infertility, menstrual irregularities and ovulation disorders, pregnancy complications, in particular, gestational diabetes. Myo-inositol plays an important role in the insulin transfer and hormone synthesis in the ovaries, in oocyte maturation, fertilization, implantation and post-implantation development. Many studies confirm the positive effect of inositol isomers on metabolic, hormonal and reproductive disorders, both in the form of monotherapy and in combination with other drugs to enhance the therapeutic effect and bioavailability. Myo-inositol has a favorable safety profile. Studies have shown that in patients with PCOS myo-inositol improves ovarian function and fertility, reduces the manifestations of hyperandrogenism, insulin resistance and normalizes weight. Myo-inositol and D-chiro-inositol have different mechanisms of action on insulin sensitivity and have different functions. The balance of the two isomers ensures the normal secretion of hormones and ovarian functioning, but it is currently unknown what the optimal ratio of these two isomers due to the small number of high quality studies and the difficulty of studying their isolated action. There are currently different combinations of myo- and D-chiro-inisotol, but they also have not been supported by enough high quality studies. When prescribing various isomers of inositol, it should be remembered that doses above 4000 mg are the most studied in patients with PCOS, but D-chiro-inositol concentration above 1200 mg/day has undesirable effects. Most studies indicate that D-chiro-inositol value is increased in PCOS, therefore oocytes are more sensitive to its overdose, and combination drugs require more study. Currently, there is no consensus in the literature on the advantage of combined supplements of myo- and D-chiro-inositol compared to monotherapy with myo-inositol. Today, myo-inositol monotherapy is more researched and safer.